Solid electrolyte layer and solid-state battery
Patent Information
- Application Number
- CN202610321713.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-16
- Filing Date
- 2026-03-17
- Publication Date
- 2026-10-23
AI Technical Summary
[0016]根据本发明的固体电解质层,能够改善固体电解质层所需特性中的一种或两种以上。
Smart Images

Figure CN122968407A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a solid electrolyte layer and a solid-state battery having a solid electrolyte layer. Background Technology
[0002] Solid-state batteries are secondary batteries that use a solid electrolyte as the electrolyte. Compared with liquid batteries that use only a liquid electrolyte, they exhibit high performance in terms of charging performance and other aspects, and have therefore attracted attention. Various solutions have been proposed to improve the performance and quality of these solid-state batteries.
[0003] For example, Japanese Patent Application Publication No. 2023-009988 discloses an all-solid-state battery comprising, in sequence, a first electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a second electrode layer. The first solid electrolyte layer has a first surface, and the second solid electrolyte layer has a second surface in contact with the first surface. The maximum height Rz1 of the first surface and the maximum height Rz2 of the second surface satisfy the relationship 0.15 ≤ Rz1 / Rz2 ≤ 0.25. Japanese Patent Application Publication No. 2023-009988 states that, according to such an all-solid-state battery, even if a crack occurs in one of the first and second solid electrolyte layers, the propagation of the crack to the other layer can be easily suppressed, thus ensuring excellent short-circuit withstand capability. Summary of the Invention
[0004] The present invention provides a novel solid electrolyte capable of improving one or more of the desired properties of a solid electrolyte layer, and a solid-state battery having such a solid electrolyte layer.
[0005] The present invention achieves the above objectives through the following means.
[0006] <Method 1>
[0007] A solid electrolyte layer having a first layer and a second layer stacked on the first layer. The first layer has an outer peripheral region and a central region located inside the outer peripheral region in the surface direction. The second layer has higher reduction resistance than the outer and central regions of the first layer, and The yield point elongation of the outer peripheral region of the first layer is greater than that of the central region of the first layer and the second layer. The ion conductivity of the central region of the first layer is greater than that of the outer peripheral region of the first layer and the second layer.
[0008] <Method 2>
[0009] According to the solid electrolyte layer of method 1, the yield point elongation of the second layer is greater than the yield point elongation of the central region of the first layer.
[0010] <Method 3>
[0011] According to the solid electrolyte layer of method 1 or 2, the ionic conductivity of the second layer is greater than the ionic conductivity of the outer peripheral region of the first layer.
[0012] Method 4
[0013] A solid-state battery, comprising, in sequence, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer according to any one of embodiments 1 to 3, and a negative electrode current collector layer.
[0014] Method 5
[0015] According to the solid-state battery described in method 4, wherein... The positive electrode active material layer is a sulfur-based positive electrode active material layer, and The solid electrolyte layer is configured such that the first layer of the solid electrolyte layer faces the positive electrode active material layer side, and the second layer of the solid electrolyte layer faces the negative electrode current collector layer side.
[0016] The solid electrolyte layer according to the present invention can improve one or more of the desired properties of the solid electrolyte layer. Attached Figure Description
[0017] The features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will now be described with reference to the accompanying drawings, in which the same reference numerals denote the same elements.
[0018] Figure 1A This is a schematic perspective view illustrating one aspect of the solid electrolyte layer of the present invention.
[0019] Figure 1B This is a schematic top view illustrating one aspect of the solid electrolyte layer of the present invention.
[0020] Figure 1C This is a schematic bottom view illustrating one aspect of the solid electrolyte layer of the present invention.
[0021] Figure 2A This is a schematic top view illustrating other aspects of the solid electrolyte layer of the present invention.
[0022] Figure 2B This is a schematic top view illustrating other aspects of the solid electrolyte layer of the present invention.
[0023] Figure 2CThis is a schematic top view illustrating other aspects of the solid electrolyte layer of the present invention.
[0024] Figure 2D This is a schematic top view illustrating other aspects of the solid electrolyte layer of the present invention.
[0025] Figure 3 This is a schematic cross-sectional view of the solid-state battery of the present invention.
[0026] Figure 4 This is a schematic top view showing the deformation pattern of the solid electrolyte layer.
[0027] Figure 5A This is a schematic perspective view illustrating another way of representing a solid electrolyte layer other than that of the present invention.
[0028] Figure 5B This is a schematic top view used to illustrate another way of using a solid electrolyte layer other than that of the present invention.
[0029] Figure 5C This is a schematic bottom view used to illustrate another way of using a solid electrolyte layer other than that of the present invention.
[0030] Figure 6A This is a schematic perspective view illustrating another way of representing a solid electrolyte layer other than that of the present invention.
[0031] Figure 6B This is a schematic top view used to illustrate another way of using a solid electrolyte layer other than that of the present invention.
[0032] Figure 6C This is a schematic bottom view used to illustrate another way of using a solid electrolyte layer other than that of the present invention. Detailed Implementation
[0033] The embodiments of the present invention will now be described in detail. However, the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the spirit of the invention.
[0034] solid electrolyte layer
[0035] The solid electrolyte layer of the present invention has a first layer and a second layer stacked on the first layer. The first layer has an outer peripheral region and a central region located in the face direction inside the outer peripheral region. The reduction resistance of the second layer is higher than that of the outer peripheral region and the central region of the first layer. Furthermore, the yield point elongation of the outer peripheral region of the first layer is greater than that of the central region of the first layer and the second layer. The ionic conductivity of the central region of the first layer is greater than that of the outer peripheral region of the first layer and the second layer.
[0036] That is, such as Figure 1A , Figure 1B , Figure 1C As illustrated, the solid electrolyte layer 100 of the present invention has a first layer 110 and a second layer 120 stacked on the first layer 110. Furthermore, the first layer 110 has an outer peripheral region 112 and a central region 114 located in the face direction inward of the outer peripheral region.
[0037] When the solid electrolyte layer is used in a solid-state battery, it experiences a significant reduction voltage near the side facing the negative electrode current collector layer. Such a reduction voltage can cause the solid electrolyte that constitutes the solid electrolyte layer to decompose and deteriorate.
[0038] In this regard, according to the solid electrolyte layer of the present invention, since the second layer has higher resistance to reduction than the outer and central regions of the first layer, when the second layer is arranged toward the negative electrode current collector layer, the decomposition and degradation of the solid electrolyte of the second layer due to reduction voltage can be suppressed.
[0039] When a solid electrolyte layer is used in a solid-state battery, a relatively large pressure is usually applied in the stacking direction to improve the contact between the active materials and the solid electrolyte. In this case, the pressure may cause the solid electrolyte layer to expand in the planar direction. Additionally, when the planar expansion and contraction of the active material layers is large, such as when using sulfide-based cathode active materials, the adjacent solid electrolyte layer may expand and contract in the planar direction along with the expansion and contraction of these active material layers during charging and discharging.
[0040] Thus, when the solid electrolyte layer expands in the planar direction, as... Figure 4 As shown, in the central region of the solid electrolyte layer 400, the deformation mode 400a is mainly radially elongated, while in the outer peripheral region, the deformation mode 400b is mainly circumferentially pushed back. Based on this deformation, as... Figure 5A , Figure 5B , Figure 5C As shown, in the solid electrolyte layer 500 of the present invention, which is uniform in the outer and central regions, radial cracks may occur in the outer peripheral region.
[0041] Furthermore, to suppress cracks in the peripheral region, a soft solid electrolyte composite material could be used to form the solid electrolyte layer 500. However, in this case, such solid electrolyte composite materials generally have low ionic conductivity. Therefore, it is difficult to simultaneously suppress radial cracks in the peripheral region and achieve good ionic conductivity in the solid electrolyte layer.
[0042] In this regard, according to the solid electrolyte layer of the present invention, since the yield point elongation of the outer peripheral region of the first layer is greater than that of the central region of the first layer and the second layer, cracks in the outer peripheral region can be suppressed. Furthermore, according to the solid electrolyte layer of the present invention, since the ionic conductivity of the central region of the first layer is greater than that of the outer peripheral region of the first layer and the second layer, the ionic conductivity of the solid electrolyte layer can be improved.
[0043] In one embodiment, in the solid electrolyte layer of the present invention, the yield point elongation of the second layer is greater than that of the central region of the first layer. This allows for the suppression of cracking in the second layer, particularly in the outer peripheral region.
[0044] Furthermore, in one embodiment, in the solid electrolyte layer of the present invention, the ionic conductivity of the second layer is greater than the ionic conductivity of the outer peripheral region of the first layer. This improves the ionic conductivity of the solid electrolyte layer.
[0045] In this invention, "peripheral region" refers to the outer peripheral region of the solid electrolyte layer. For example, based on the longest diameter in the surface direction of the solid electrolyte layer, the "peripheral region" can be a region with a width of less than 40%, less than 30%, less than 20%, or less than 10% of the longest diameter starting from the outer periphery. Alternatively, the "peripheral region" can also be a region with a width of more than 5%, more than 10%, more than 20%, more than 30%, or more than 35% of the longest diameter starting from the outer periphery.
[0046] When the solid electrolyte layer of the present invention has a rectangular or square shape in the planar direction, the outer peripheral region along the long side can be a region with a width of less than 40%, less than 30%, less than 20%, or less than 10% of the length of the short side from the long side. Alternatively, the outer peripheral region along the long side can also be a region with a width of more than 5%, more than 10%, more than 20%, more than 30%, or more than 35% of the length of the short side from the long side.
[0047] Furthermore, in this case, the outer perimeter region along the short side can be a region with a width of less than 40%, 30%, 20%, or 10% of the length of the long side, starting from the short side. Alternatively, the outer perimeter region along the short side can also be a region with a width of more than 5%, 10%, 20%, 30%, or 35% of the length of the long side, starting from the short side.
[0048] When the solid electrolyte layer of the present invention is circular or elliptical in the planar direction, the outer peripheral region can be a region with a width of less than 40%, less than 30%, less than 20%, or less than 10% of the radius (or minor axis or major axis) from the outer periphery. Alternatively, the outer peripheral region can also be a region with a width of more than 5%, more than 10%, more than 20%, more than 30%, or more than 35% of the radius from the outer periphery.
[0049] In addition, the area of the "peripheral region" can be, for example, more than 5% of the area in the direction of the solid electrolyte layer, more than 10% of the area, more than 20% of the area, more than 30% of the area, more than 40% of the area, or more than 50% of the area, and can also be less than 60% of the area, less than 50% of the area, less than 40% of the area, less than 30% of the area, or less than 20% of the area.
[0050] In this invention, the "central region" refers to the region located inside the surface of the outer peripheral region.
[0051] In this invention, the "solid electrolyte layer" can have any shape in the planar direction, for example, it can be circular. Figure 2A and Figure 2B ), oval, rectangular ( Figure 2C ), square, rounded rectangle ( Figure 2D Shapes such as rounded squares, etc. Furthermore, as mentioned above, the size of the "outer perimeter region" and the size of the "central region" can be arbitrarily chosen; therefore, in the surface direction, shapes such as... Figure 2A That way, the outer perimeter area is smaller, and it can also be like Figure 2B That would result in a larger outer perimeter area. It should be noted that... Figure 2A , Figure 2B , Figure 2C , Figure 2D The solid electrolyte layers 100a, 100b, 100c and 100d of the present invention are shown to have outer peripheral regions 112a, 112b, 112c and 112d of the first layer and central regions 114a, 114b, 114c and 114d located inside the surface of the outer peripheral regions.
[0052] In this invention, the "yield point elongation" of each part of the solid electrolyte layer refers to the elongation value of the test sample when it reaches the yield point after a tensile test on each part. Therefore, the magnitude of the "yield point elongation" of the solid electrolyte layer indicates the degree to which cracks are less likely to occur when tensile stress is applied.
[0053] Specifically, in this invention, the "yield point elongation" can be evaluated as follows: The solid electrolyte layer is cut into strips of 5mm × 20mm using a cutting machine. Two strips are then laminated together and transferred using a uniaxial press at 84kN to create a test sample. The test sample is mounted on the fixture of a tensile compression testing machine (micro-autograph) with a mark spacing of 20mm. A tensile test is performed at a tensile speed of 5mm / min until the test sample reaches its yield point. The elongation of the test sample at the yield point is then measured. It should be noted that, to avoid moisture causing degradation of the solid electrolyte, the test can be completed within 5 minutes in a dry chamber environment with a dew point below -45°C.
[0054] In this invention, the "ionic conductivity" of the solid electrolyte layer refers to the value obtained by measuring the ionic conductivity of test samples of various parts of the solid electrolyte layer. Here, the ions whose ionic conductivity is measured are the ions used as carrier ions in a solid-state battery intended to use the solid electrolyte of this invention. Therefore, when the solid electrolyte of this invention is intended to be used in a lithium-ion battery, the ions whose ionic conductivity is measured are lithium ions.
[0055] Specifically, in this invention, "ionic conductivity" is evaluated as follows: 100 mg of the material constituting the solid electrolyte layer is weighed and placed in a Φ11.28 mm Macor, and pressed with approximately 10 kN. Then, carbon-coated aluminum foil is placed on both sides of the solid electrolyte layer, pressed with 42 kN, and dimensionally constrained with a constraint pressure of 6 Nm to fabricate a plate cell. Next, the resistance value is measured by AC impedance spectroscopy, and the ionic conductivity is calculated. It should be noted that when reading the resistance value, if an arc component is observed in the Nyquist plot, the resistance value at the frequency where the imaginary part Z on the low-frequency side of the first arc component is at its minimum is read as the resistance value R (Ω). Alternatively, if no arc component is observed in the Nyquist plot, the resistance value at a frequency of 100 kHz is read as the resistance value R (Ω). Based on the resistance value R (Ω) read in the above steps and the evaluated dimensions of the solid electrolyte layer, the resistivity ρ is calculated, and the ionic conductivity is calculated from the reciprocal of the resistivity ρ.
[0056] In this invention, the "resistance to reduction" of the solid electrolyte layer is an indicator of how easily the solid electrolyte contained in each test sample is decomposed and degraded when a reduction voltage is applied to the test sample in each part of the solid electrolyte layer. This "resistance to reduction" can be examined by applying a reduction voltage to the test sample in each region and observing the magnitude of the reduction potential at which the solid electrolyte contained therein begins to decompose and degrade.
[0057] In this invention, the "yield point elongation", "ionic conductivity" and "reduction resistance" of the solid electrolyte layer can be adjusted by adjusting the type and amount of materials used in the solid electrolyte layer, especially the type and amount of solid electrolyte and the type and amount of binder.
[0058] To address this, for example, to increase the "yield point elongation" of the solid electrolyte layer, a highly elastic solid electrolyte can be used as the solid electrolyte layer, a highly elastic binder can be used as the binder in the solid electrolyte layer, and the amount of binder used in the solid electrolyte layer can be increased. Examples of solid electrolytes with such a high "yield point elongation" include, for instance, lithium thio-LiSICON type solid electrolytes containing LiI.
[0059] Furthermore, for example, to increase the "ionic conductivity" of the solid electrolyte layer, a solid electrolyte with high ionic conductivity can be used as the solid electrolyte in the solid electrolyte layer, which can reduce the amount of binder used in the solid electrolyte layer. Li can be cited as an example of such a solid electrolyte with high "ionic conductivity". 10 GeP2S 12 wait.
[0060] Additionally, for example, to improve the "reduction resistance" of the solid electrolyte layer, a solid electrolyte with high reduction resistance can be used as the solid electrolyte in the solid electrolyte layer. Examples of such solid electrolytes with high "reduction resistance" include sulfide-germanium ore type solid electrolytes containing LiCl and LiBr, lithium thiosulfate superionic conductor type solid electrolytes containing LiI, and especially sulfide-germanium ore type solid electrolytes containing LiCl and LiBr.
[0061] The shape of the solid electrolyte layer is not particularly limited; for example, it can be a sheet with a generally planar surface. The thickness of the solid electrolyte layer is not particularly limited; for example, it can be 0.1 μm or more, 1 μm or more, or 10 μm or more, or it can be less than 2 mm, less than 1 mm, or less than 500 μm.
[0062] solid electrolyte
[0063] The solid electrolyte used in the solid electrolyte layer of the present invention can be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, inorganic solid electrolytes exhibit excellent ionic conductivity and heat resistance. Examples of inorganic solid electrolytes include oxide solid electrolytes, sulfide solid electrolytes, and ionically bonded inorganic solid electrolytes. Among inorganic solid electrolytes, sulfide solid electrolytes, and especially those containing at least Li, S, and P as constituent elements, exhibit superior performance. Alternatively, among inorganic solid electrolytes, ionically bonded solid electrolytes, and especially those containing at least Li, Y, and a halogen (at least one of Cl, Br, I, and F) as constituent elements, exhibit superior performance. The solid electrolyte can be amorphous or crystalline.
[0064] The particle size of the solid electrolyte can be less than 1.0 μm, less than 0.9 μm, less than 0.8 μm, less than 0.7 μm, or less than 0.5 μm, or greater than 0.1 μm, 0.2 μm, or 0.3 μm. The particle size of the solid electrolyte is the particle size (median diameter) that accounts for 50% of the cumulative value in the volume-based particle size distribution obtained by laser diffraction / scattering method.
[0065] The oxide solid electrolyte can be selected from lithium lanthanum zirconate, LiPON, Li 1+x Al x Ge 2-x One or more of the following: (PO4)3, Li-SiO glass, and Li-Al-SO glass. Furthermore, when oxide solid electrolytes are combined with liquid electrolytes, ionic conductivity can be improved.
[0066] Sulfide solid electrolytes may contain, for example, Li, X (where X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. Furthermore, sulfide solid electrolytes may further contain at least one of O and a halogen. Additionally, sulfide solid electrolytes may contain S as the main component of the anionic element.
[0067] Sulfide solid electrolytes can be selected from, for example, Li₂S-P₂S₅, Li₂S-P₂S₅-LiI, Li₂S-P₂S₅-GeS₂, Li₂S-P₂S₅-Li₂O, Li₂S-P₂S₅-Li₂O-LiI, Li₂S-P₂S₅-LiBr, Li₂S-SiS₂, Li₂S-SiS₂-LiI, Li₂S-SiS₂-LiBr, Li₂S-SiS₂-LiCl, Li₂S-SiS₂-B₂S₃-LiI, Li₂S-SiS₂-P₂S₅-LiI, Li₂S-B₂S₃, and Li₂S-P₂S₅-Z. mS n (Where m and n are positive numbers. Z is any one of Ge, Zn, and Ga.) Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (Where x and y are positive numbers. M is any one of P, Si, Ge, B, Al, Ga, and In.)
[0068] In the solid electrolyte layer of the present invention, at least a portion of the solid electrolyte can be self-formed during the first charge of the solid-state battery having the solid electrolyte layer. That is, the solid electrolyte layer of the present invention contains a phosphorus-containing sulfide, such as P2S5, before the first charge, which reacts at least partially with lithium during the first charge to form a sulfide solid electrolyte as described above. A solid electrolyte that self-forms during the first charge in this manner provides a suitable ion conduction network and is therefore preferred.
[0069] Regarding phosphorus-containing sulfides, as constitutive elements, they may contain at least phosphorus and sulfur, and may further contain other elements. Examples of other elements include one or more of Ge, Sn, Si, B, and Al. Furthermore, phosphorus-containing sulfides may contain phosphorus and sulfur, as well as the aforementioned other elements, but may not contain lithium. P₂S₅ is an example of a phosphorus-containing sulfide. Additionally, phosphorus-containing sulfides may have a positive phosphorus structure (PS₄ structure). The shape of phosphorus-containing sulfides is not particularly limited; for example, they may be granular.
[0070] The content of solid electrolyte in each part of the solid electrolyte layer is not particularly limited and can be appropriately determined according to the required performance of the solid electrolyte layer. Regarding the content of solid electrolyte, for example, it can be 1% or more, 5% or more, 10% or more, 15% or more, or 20% or more relative to the solid electrolyte layer, or it can be less than 95% or less, 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less.
[0071] resin adhesive
[0072] In addition to the solid electrolyte mentioned above, each part of the solid electrolyte layer may optionally have a resin binder.
[0073] The resin adhesive used herein is not particularly limited, and may be selected from one or more of butadiene rubber, butene rubber, acrylonitrile-butadiene rubber, acrylate-butadiene rubber, styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyimide, etc.
[0074] In each part of the solid electrolyte layer, the content of resin binder can be 0.1% by mass or more and 15% by mass or less. When the solid electrolyte layer contains more resin binder, the flexibility of the solid electrolyte layer increases, but the ionic conductivity decreases. The above-mentioned content can be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 3% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, or 10% by mass or less, or less than 15% by mass, less than 14% by mass, less than 13% by mass, less than 12% by mass, or less than 11% by mass.
[0075] Manufacturing method of solid electrolyte layer
[0076] The solid electrolyte layer can be formed, for example, by dry or wet molding of a solid electrolyte composite material containing the aforementioned solid electrolyte and resin binder.
[0077] solid-state batteries
[0078] The solid-state battery of the present invention comprises, in sequence, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer of the present invention, and a negative electrode current collector layer.
[0079] That is, such as Figure 3 As illustrated, the solid-state battery 1000 of the present invention sequentially comprises a positive electrode current collector layer 310, a positive electrode active material layer 320, a solid electrolyte layer 100 of the present invention, an optional negative electrode active material layer 330, and a negative electrode current collector layer 340.
[0080] In the solid-state battery of the present invention, the negative electrode active material layer 330 may not be used, and carrier ions may be dissolved and precipitated at that location. That is, for example, when the carrier ion is lithium ion, during the discharge of the solid-state battery, the lithium metal layer between the solid electrolyte layer and the negative electrode current collector layer is converted into lithium ions, which are then inserted into the positive electrode active material layer via the solid electrolyte layer. In addition, during the charging of the solid-state battery, lithium ions are deintercalated from the positive electrode active material layer, and lithium metal is deposited between the solid electrolyte layer and the negative electrode current collector layer to form a lithium metal layer.
[0081] The solid-state battery of the present invention may be, for example, a solid-state battery using lithium as the carrier ion, i.e., a solid-state lithium battery, or a solid-state battery using sodium as the carrier ion, i.e., a solid-state sodium battery.
[0082] The solid-state battery according to the present invention can achieve the effects brought about by the solid electrolyte layer of the present invention.
[0083] It should be noted that, in this invention, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as the electrolyte. Therefore, a solid-state battery can use a combination of solid and liquid electrolytes as the electrolyte. Additionally, in this invention, a "solid-state battery" can also be an all-solid-state battery, that is, a battery that uses only a solid electrolyte as the electrolyte.
[0084] In one embodiment, the positive electrode active material layer is a sulfur-based positive electrode active material layer, and the solid electrolyte layer is configured such that the first layer of the solid electrolyte layer faces the positive electrode active material layer side, and the second layer of the solid electrolyte layer faces the negative electrode current collector layer side.
[0085] As described above regarding the solid electrolyte layer in this invention, when the expansion and contraction of the active material layer is large, for example, when a sulfur-based positive electrode active material is used as the positive electrode active material, the adjacent solid electrolyte layer may expand and contract in the planar direction along with the expansion and contraction of the active material layer during charging and discharging, which may lead to cracks in the solid electrolyte layer.
[0086] In this regard, according to the solid-state battery of the present invention as described above, by arranging the solid electrolyte layer such that the first solid electrolyte layer with a larger yield point elongation is positioned toward the sulfur-based positive electrode active material layer, i.e., the active material layer side which expands and contracts significantly during charging and discharging, cracking of the solid electrolyte layer in the portion on the positive electrode active material layer side can be suppressed.
[0087] Positive current collector layer
[0088] The shape of the positive electrode current collector layer used in the solid-state battery of the present invention is not particularly limited; for example, it can be foil-shaped or plate-shaped. The positive electrode current collector layer can be composed of two or more foils or layers. The positive electrode current collector layer can have a metal foil or a layer composed of a resin composition containing a resin and conductive additives.
[0089] Examples of metals constituting the metal foil include at least one selected from Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, V, Mg, Pb, Ge, In, Sn, Zr, and stainless steel. In particular, from the viewpoint of ensuring oxidation resistance, Al is preferred. The positive current collector layer can be a layer formed by depositing or vapor-depositing the aforementioned metal onto the metal foil or substrate.
[0090] There is no particular limitation on the thickness of the positive electrode current collector layer; it can be greater than 0.1μm or greater than 1μm, or less than 1mm or less than 100μm.
[0091] Positive electrode active material layer
[0092] The positive electrode active material layer used in the solid-state battery of the present invention comprises a positive electrode active material, a solid electrolyte, and a resin binder that binds them together. The positive electrode active material layer may further comprise other active materials, conductive additives, etc. Furthermore, any positive electrode active material can be used, such as oxide-based positive electrode active materials like nickel-manganese-cobalt composite oxides, sulfur-based active materials, etc., and in particular, sulfur-based active materials can be used.
[0093] The shape of the positive electrode active material layer is not particularly limited; for example, it can be a sheet with a generally planar shape. The thickness of the positive electrode active material layer is not particularly limited; for example, it can be 0.1 μm or more, 1 μm or more, or 10 μm or more, or it can be less than 2 mm, less than 1 mm, or less than 500 μm.
[0094] sulfur-based active substances
[0095] The sulfur-based active material contained in the positive electrode active material layer is acceptable as long as it reacts with lithium ions, which serve as charge compensation ions, during discharge to generate a compound containing sulfur and lithium (such as sulfides like Li₂S) as a discharge product, and can release lithium ions during charging. Positive electrode active material layers containing such sulfur-based active materials typically exhibit significant surface expansion and contraction during charging and discharging, and therefore can preferably be used in combination with the solid electrolyte layer of this invention.
[0096] Sulfur-based reactive substances can contain elemental sulfur or be composed of elemental sulfur. Elemental sulfur can be cyclooctasulfide (S8) or other substances. Cyclooctasulfide (S8) can be α-sulfur, β-sulfur, γ-sulfur, or a combination thereof.
[0097] Sulfur-based active substances can be dissolved in solid electrolytes or chemically bonded to solid electrolytes. For example, when the solid electrolyte is a phosphorus-containing sulfide such as phosphorus pentasulfide (P2S5), the sulfur in the sulfur-based active substance can be chemically bonded to the sulfur in the phosphorus-containing sulfide.
[0098] The shape of the sulfide-based active material is not particularly limited; for example, it can be particulate. The particle size of the sulfide-based active material can be, for example, greater than 1 nm, greater than 5 nm, or greater than 10 nm, and can be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm. It should be noted that the particle size of the positive electrode active material is the particle size (median diameter) at the 50% cumulative value of the volume-based particle size distribution obtained by laser diffraction / scattering method.
[0099] The content of sulfur-based active materials in the positive electrode active material layer can be appropriately determined according to the target battery performance. For example, relative to the positive electrode active material layer, the content of sulfur-based active materials can be more than 10% by mass, more than 20%, more than 30%, more than 40% by mass, more than 50% by mass, or more than 60% by mass, or it can be less than 100% by mass or less than 90% by mass.
[0100] solid electrolyte
[0101] Regarding solid electrolytes, please refer to the description of the solid electrolyte layer of the present invention.
[0102] resin adhesive
[0103] Regarding the resin binder, please refer to the description of the solid electrolyte layer of the present invention.
[0104] Conductive additives
[0105] The conductive additive is not particularly limited and can be, for example, carbon. Carbon can be, for example, one or more of carbon nanotubes, vapor-grown carbon fibers (VGCF), acetylene black, furnace black, Ketjen black, activated carbon, and graphene. In particular, when the positive electrode active material layer contains carbon nanotubes, high battery performance is easily ensured. Other conductive additives include, for example, one or more conductive additives composed of various metallic materials. The conductive additive can be, for example, in particulate or fibrous form, and its size is not particularly limited.
[0106] Method for manufacturing positive electrode active material layer
[0107] The positive electrode active material layer can be manufactured using known methods. For example, the positive electrode active material layer can be formed by dry or wet molding of a positive electrode composite material containing the above-mentioned components. The positive electrode active material layer can be formed on the positive electrode current collector layer or formed separately from the positive electrode current collector layer.
[0108] Negative electrode active material layer / lithium metal layer
[0109] The negative electrode active material layer used in the solid-state battery of the present invention may comprise a negative electrode active material, a solid electrolyte, and a resin binder that bonds them together. The negative electrode active material layer may further comprise other active materials, conductive additives, etc.
[0110] As a negative electrode active material, not only carbon can be used, but also alloy-based negative electrode active materials such as silicon.
[0111] Furthermore, in the solid-state battery of the present invention, a lithium metal layer composed of metallic lithium can be used instead of the negative electrode active material layer. In this case, during charging, lithium ions migrating from the positive electrode active material layer accept electrons and are deposited as metallic lithium between the solid electrolyte layer and the negative electrode current collector layer, forming a lithium metal layer. During discharging, the lithium between the solid electrolyte layer and the negative electrode current collector layer is ionized and returns to the positive electrode active material layer.
[0112] Negative current collector layer
[0113] The negative electrode current collector layer can be a metal foil or a metal mesh, or it can be a carbon sheet. In particular, from an operational point of view, a metal foil is preferred. The negative electrode current collector layer can be composed of two or more metal foils or sheets, and when the negative electrode current collector layer is composed of two or more metal foils or sheets, there can be any layer between the two or more metal foils.
[0114] Examples of metals constituting the metal foil include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel. In particular, from the viewpoint of ensuring resistance to reduction and resistance to alloying with lithium, it is preferable to include at least one metal selected from Cu, Ni, and stainless steel, and especially preferable to include at least one metal selected from Ni and stainless steel.
[0115] There is no particular limitation on the thickness of the negative electrode current collector layer; it can be greater than 0.1μm or greater than 1μm, or less than 1mm or less than 100μm.
[0116] Making with Figure 1A , Figure 1B , Figure 1C The solid electrolyte layer of the embodiment shown has Figure 5A , Figure 5B , Figure 5C The solid electrolyte layer of the comparative example shown, and the one having Figure 6A , Figure 6B , Figure 6C The solid electrolyte layer of the comparative example shown is evaluated, and the resulting solid electrolyte layer or solid-state battery having such a solid electrolyte layer is evaluated.
[0117] Specifically, the solid electrolyte layer and solid-state battery of the embodiments and comparative examples are fabricated as follows.
[0118] Fabrication of solid electrolyte layer
[0119] Acrylonitrile-butadiene rubber (ABR) solution and dibutyl ether, used as resin binders, were added to a polypropylene container and mixed using a shaker for 3 minutes. After adding the solid electrolyte, the mixture was further mixed using a shaker and ultrasonic dispersion device, with appropriate amounts of solvent added. This process was repeated until a suitable dispersion was achieved, thus preparing a solid electrolyte composite slurry. Next, the solid electrolyte composite slurry was coated onto a release film foil using a doctor blade with a coating gap of 450 μm. After visually confirming surface dryness, the slurry was dried on a hot plate at 165°C for 1 hour.
[0120] The horizontal zonal coating of the solid electrolyte layer was performed using an intermittent coating method with a die-casting machine. Specifically, two concentric circles were used to horizontally divide the layer into two regions. The area from the center to 40% of the radius was designated as the central region, and the remaining area as the outer perimeter. After coating, the same drying method as blade coating was used. The vertical zonal coating was performed using a stack coating method. The thickness of all solid electrolyte layers after drying was 95–100 μm, and the thickness of each solid electrolyte layer when two layers were stacked was 45–50 μm.
[0121] For the solid electrolyte layers of the embodiments and comparative examples obtained above, the ionic conductivity was evaluated as described above.
[0122] Fabrication of the positive electrode active material layer
[0123] Sulfur (vacuum-dried at 80°C), P2S5, and carbon nanotubes (diameter less than 2nm, vacuum-dried at 120°C) were mixed in a mortar at a weight ratio of 42:35:23. 1.7g of this mixture and 80g of Φ4mm zirconia balls were added to each milling jar. Two such jars were used, and the mixture was ball-milled at 400rpm using a planetary ball mill for a total of 36 hours (one hour of rotation followed by a 15-minute pause, repeated 36 times, with reverse rotation). After ball milling, the mixture was dry-graded using a 38μm sieve to obtain the sulfur cathode composite material.
[0124] Trimethylbenzene as a solvent, the above-mentioned sulfur cathode composite material, and a binder were mixed in a mass ratio of 99.7:0.3 to prepare a cathode composite material slurry. The cathode composite material slurry was coated onto a roughened aluminum foil with a gap of 220 μm, pre-dried at 50°C, and then formally dried at 100°C for 30 minutes to obtain a sulfide-based cathode active material layer coated on the cathode current collector foil.
[0125] Fabrication of laminated battery cells
[0126] On a self-supporting film (approximately 70 μm thick) obtained by pressing a solid electrolyte layer (circular in diameter 14.5 mm) prepared above using a uniaxial press at 58.8 kN, a lithium-magnesium alloy foil (circular in diameter 13 mm, 100 μm thick) as the negative electrode active material layer and a roughened nickel foil (14.5 mm in diameter) as the negative electrode current collector layer are placed. The layers are then gently pressed together using a 0.1 t press. Next, a sulfide-based positive electrode active material layer (13 mm in diameter) prepared above is placed on the solid electrolyte layer side of the resulting laminate. The laminate is then vacuum-sealed within the laminate material and pressurized at 300 MPa using a cold isostatic press (CIP) to fabricate a laminated battery cell. This laminated battery cell is constrained at 5 MPa for charge-discharge evaluation.
[0127] evaluate
[0128] For the laminated battery cell obtained above, after being placed in an open-circuit (OCV) state for 3 hours, the cutoff voltage is 3.1–1.2V (vs Li / Li). + Within the specified range, the circuit was discharged to 1.2V at a current density of 0.584 mA / cm², equivalent to 0.1C (1C = 5.84 mA / cm²), and at 60°C. Afterward, it was charged at the same rate, and cycle performance was assessed by varying the voltage.
[0129] The evaluation criteria and results are summarized in Table 1 below. It should be noted that when the cycle performance is poor, the speculated reasons are recorded in parentheses.
[0130] (Table 1)
[0131] It should be noted that the solid electrolyte composite materials A to C used in the examples and comparative examples are as follows.
[0132] (Table 2)
[0133] As shown in Tables 1 and 2, the solid-state battery using the solid electrolyte layer of the embodiment achieved good cycle characteristics, while the solid-state battery using the solid electrolyte layer of the comparative example failed to achieve good cycle characteristics.
Claims
1. A solid electrolyte layer having a first layer and a second layer stacked on the first layer, The first layer has an outer peripheral region and a central region located inside the outer peripheral region in the surface direction. The second layer has higher reduction resistance than the outer and central regions of the first layer, and The yield point elongation of the outer peripheral region of the first layer is greater than that of the central region of the first layer and the second layer. The ion conductivity of the central region of the first layer is greater than that of the outer peripheral region of the first layer and the second layer.
2. The solid electrolyte layer according to claim 1, wherein, The yield point elongation of the second layer is greater than that of the central region of the first layer.
3. The solid electrolyte layer according to claim 1, wherein, The ionic conductivity of the second layer is greater than that of the outer peripheral region of the first layer.
4. A solid-state battery, comprising, in sequence, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer according to any one of claims 1 to 3, and a negative electrode current collector layer.
5. The solid-state battery according to claim 4, wherein, The positive electrode active material layer is a sulfur-based positive electrode active material layer, and The solid electrolyte layer is configured such that the first layer of the solid electrolyte layer faces the positive electrode active material layer side, and the second layer of the solid electrolyte layer faces the negative electrode current collector layer side.
Citation Information
Patent Citations
All-solid battery and manufacturing method thereof
JP2023009988A
